The Effect of The Number of Taxable Enterprise, Tax Audit, Tax Collection On Value Added Tax Receiving - Alferdio Haidarputra; Indra Pahala; Indah Muliasari (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study aims to provide empirical evidence about the effect of taxable enterprise, tax audits, tax  collection  on  value  added  tax  revenues.This  research  uses  sampling  method  with  saturated sampling  technique. The  population  in  this  study  used  all  taxable enterprise registered  at  KPP Pratama Jakarta Setiabudi Empat. The sample used in this study was 36 data using the Time series data  type. The  statistical  method  used  is  multiple  linear  regression  analysis  with  SPSS  calculator. The results of this study indicate that taxable enterprise, tax audits, and tax collection have an effect on value added tax revenues.